A molecular nanocap activated by superparamagnetic heating for externally stimulated cargo release. Issue 9 (15th December 2015) - Rühle, B.; Datz, S.; Argyo, C.; Bein, T.; Zink, J. I.
Abstract : A novel thermoresponsive snaptop for stimulated cargo release from superparamagnetic iron oxide core – mesoporous silica shell nanoparticles based on a [2 + 4] cycloreversion reaction (retro-Diels Alder reaction) is presented. Abstract : A novel thermoresponsive snaptop for stimulated cargo release from superparamagnetic iron oxide core – mesoporous silica shell nanoparticles based on a [2 + 4] cycloreversion reaction (retro-Diels Alder reaction) is presented. The non-invasive external actuation through alternating magnetic fields makes this material a promising candidate for future applications in externally triggered drug delivery.